Detection of bacterial DNA by in situ hybridization in patients with decompensated liver cirrhosis - Shingo Usui; Hirotoshi Ebinuma; Po-Sung Chu; Nobuhiro Nakamoto; Yoshiyuki Yamagishi; Hidetsugu Saito; Takanori Kanai (BMC Gastroenterology, 2017)
Abstract Background Spontaneous bacterial peritonitis (SBP) is often difficult to diagnose because bacteria in ascites cannot be detected accurately by conventional culture. In situ hybridization (ISH) was previously developed for rapid detection of genes from bacteria phagocytized by neutrophils. SBP may develop after bacteria enter into the systemic circulation following bacterial translocation. Therefore, we performed ISH to identify bacteria in blood samples collected from patients with decompensated liver cirrhosis (LC). Methods In this retrospective study, peripheral blood samples were collected from 60 patients with decompensated LC, and bacteria were detected by both blood culture and ISH. Moreover, 35 patients underwent paracentesis for diagnosis of SBP. Results Eight of 35 patients were diagnosed with SBP by polymorphonuclear neutrophil counts, and one patient was diagnosed with bacterascites. Seven of the nine patients showed positive results for ISH, whereas bacteria were detected in only two cases by blood culture. Thirty-seven of 60 cases (62%) showed positive results for ISH, whereas only six samples (10%) were positive by blood culture analysis. Compared with the 23 cases of negative ISH, the 37 cases of positive ISH showed a higher frequency of fever, higher Child-Pugh scores, and lower albumin levels. Conclusions Detection of bacteria by ISH suggested that bacterial translocation, which cannot be proven by conventional culture, occurred in these patients, and that ISH could be helpful for the early diagnosis of some types of infection and prevention of SBP in these patients.